1992
DOI: 10.1111/j.1467-8624.1992.tb03595.x
|View full text |Cite
|
Sign up to set email alerts
|

Sibling Delinquency and the Family Environment: Shared and Unshared Influences

Abstract: Few family studies of delinquency have focused on siblings. We use a sibling research design to evaluate shared (i.e., family) and unshared environmental influences on delinquency. The 15-22-year-old adolescent siblings were nationally representative, and uniquely, in families of 2 to 4 siblings. No unshared family environmental influences were found for sisters and for mixed-sex siblings, but they may exist for brothers. The data suggested substantial shared environmental and/or shared genetic influences for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 24 publications
6
35
0
Order By: Relevance
“…These results suggest that some familial factors may be influential in the etiology of peer group characteristics such as popularity and college and delinquency orientation and are in line with past research indicating significant shared familial influences on adolescent self-reported delinquency (Rowe, Rodgers, & Meseck-Bushey, 1992). The specific source of this shared familial influence is, however, unknown.…”
Section: Discussionsupporting
confidence: 86%
“…These results suggest that some familial factors may be influential in the etiology of peer group characteristics such as popularity and college and delinquency orientation and are in line with past research indicating significant shared familial influences on adolescent self-reported delinquency (Rowe, Rodgers, & Meseck-Bushey, 1992). The specific source of this shared familial influence is, however, unknown.…”
Section: Discussionsupporting
confidence: 86%
“…The 12 SRD items administered to the mother were: hit or seriously threatened to hit someone; attacked someone with the idea of seriously hurting or killing them; got into a physical fight at school or work; used force or strong-arm methods to get money or things from a person; took something from a store without paying for it; other than shoplifting, took something worth less than $50; other than shoplifting, took something not belonging to you worth $50 or more; purposely destroyed or damaged property; took a vehicle for a ride without the owner's permission; broke into a building or vehicle to steal something or just to look around; sold marijuana or hashish; and sold hard drugs. In the NLSY parent generation sample, Cronbach's alpha for the SRD was .77 (Rowe, Rodgers, & Mesech-Bushey, 1992). Although self-reports of delinquency are not perfect measures, they are widely regarded by delinquency researchers as more valid than official police and courts statistics, which are often incomplete and biased by family income, race-ethnicity, sex, age, and other factors that influence which delinquent youth are arrested and convicted (Babinski, Hartsough, & Lambert, 1999;Loeber et al, 1998;McCord, 1990).…”
Section: Maternal Delinquencymentioning
confidence: 97%
“…Specifically, our study included children with delinquent siblings, a group that has proven to be at significant risk for antisocial behavior (Bank et al, 2004;Compton, Snyder, Schrepferman, Bank, & Shortt, 2003;Conger & Rueter, 1996;Patterson, 1984;Reid, Patterson, & Snyder, 2002;Reiss, Neiderhiser, Hetherington, & Plomin, 2000;Rodgers et al, 2001;Rowe, Almeida, & Jacobson, 1999;Rowe, Rodgers, & Meseck-Bushey, 1992;Slomkowski et al, 2001;Wasserman, Miller, Pinner, & Jaramillo, 1996).…”
Section: Preventive Intervention For Preschoolers At High Risk For Anmentioning
confidence: 98%